Incidence of Venous Thromboembolism Based on Caprini Score in Deep Inferior Epigastric Perforator Flap Breast Reconstruction - Wu, Shannon S.; Raymer, Charles; Schafer, Rachel; Culbert, August; Bernard, Steven; Djohan, Risal; Schwarz, Graham; Bishop, Sarah N.; Gurunian, Raffi (Journal of Reconstructive Microsurgery, 2023)
Background Deep inferior epigastric perforator (DIEP) flaps are commonly used for autologous breast reconstruction, but reported rates of venous thromboembolism (VTE) are up to 6.8%. This study aimed to determine the incidence of VTE based on preoperative Caprini score following DIEP breast reconstruction.Methods This retrospective study included patients who underwent DIEP flaps for breast reconstruction between January 1, 2016 and December 31, 2020 at a tertiary-level, academic institution. Demographics, operative characteristics, and VTE events were recorded. Receiver operating characteristic analysis was performed to determine the area under the curve (AUC) of the Caprini score for VTE. Univariate and multivariate analyses assessed risk factors associated with VTE.Results This study included 524 patients (mean age 51.2 ± 9.6 years). There were 123 (23.5%) patients with the Caprini score of 0 to 4, 366 (69.8%) with scores 5 to 6, 27 (5.2%) with scores 7 to 8, and 8 (1.5%) patients with scores >8. Postoperative VTE occurred in 11 (2.1%) patients, at a median time of 9 days (range 1–30) after surgery. VTE incidence by the Caprini score was 1.9% for scores 3 to 4, 0.8% for scores 5 to 6, 3.3% for scores 7 to 8, and 13% for scores >8. The Caprini score achieved an AUC of 0.70. A Caprini score >8 was significantly predictive of VTE on multivariable analysis relative to scores 5 to 6 (odds ratio = 43.41, 95% confidence interval = 7.46–252.76, p < 0.001).Conclusion In patients undergoing DIEP breast reconstruction, VTE incidence was highest (13%) in Caprini scores greater than eight despite chemoprophylaxis. Future studies are needed to assess the role of extended chemoprophylaxis in patients with high Caprini scores.
Keywords: breast reconstruction; Caprini score; deep inferior epigastric perforator; deep venous thrombosis; venous thromboembolism